Cell wall modifications during osmotic stress in Lactobacillus casei - Piuri, M. (2005)
Aims: To study the modification of the cell wall of Lactobacillus casei ATCC 393 grown in high salt conditions. Methods and Results: Differences in the overall structure of cell wall between growth in high salt (MRS + 1 mol l -1 NaCl; N condition) and control (MRS; C condition) conditions were determined by transmission electronic microscopy and analytical procedures. Lactobacillus casei cells grown in N condition were significantly larger than cells grown under unstressed C condition. Increased sensitivity to mutanolysin and antibiotics with target in the cell wall was observed in N condition. Purified cell wall also showed the increased sensitivity to lysis by mutanolysin. Analysis of peptidoglycan (PG) from stressed cells showed that modification was at the structural level in accordance with a decreased PG cross-link involving penicillin-binding proteins (PBP). Nine PBP were first described in this species and these proteins were expressed in low percentages or presented a modified pattern of saturation with penicillin G (Pen G) during growth in high salt. Three of the essential PBP were fully saturated in N condition at lower Pen G concentrations than in C condition, suggesting differences in functionality in vivo. Conclusions: The results show that growth in high salt modified the structural properties of the cell wall. Significance and Impact of Study: Advances in understanding the adaptation to high osmolarity, in particular those involving sensitivity to lysis of lactic acid bacteria.